Able To Allocate And Use Time - Naomi Rose Mariani Silaban; Dorlan Naibaho (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
This article discusses In the midst of an ever-changing business environment, society is under great pressure. Especially in companies with very active business activities, many responsibilities need to be carried out. In a competitive industry, business leaders must do this. Manage your time well so you can survive and progress sustainably. The concept of time management began during the Industrial Revolution and became a modern way of thinking about getting things done. Effective and efficient. Time management is one of the basic skills needed for you to be successful in life. The results of various studies show that time management is beneficial for organizations/companies learning to compete and achieving great success in business.